Capital requirements, risk-taking and welfare in a growing economy - Pierre-Richard Agénor; Luiz A. Pereira da Silva (Inter-American Development Bank (IDB), 2017)
The effects of capital requirements on risk-taking and welfare are studied in a stochastic overlapping generations model of endogenous growth with banking, limited liability, and government guarantees. Capital producers face a choice between a safe technology and a risky (but socially inefficient) technology, and bank risk-taking is endogenous. Setting the capital adequacy ratio above a structural threshold can eliminate the equilibrium with risky loans (and thus inefficient risk-taking), but numerical simulations show that this may entail a welfare loss. In addition, the optimal ratio may be too high in practice and may concomitantly require a broadening of the perimeter of regulation and a strengthening of financial supervision to prevent disintermediation and distortions in financial markets.
Keywords: E44; G28; O41; 330; Capital requirements; Bank risk-taking; Growth and welfare